PROSPECTS FOR THE DEVELOPMENT OF AGRICULTURE IN THE REGIONS BASED ON THE INTRODUCTION OF INFORMATION TECHNOLOGY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
As the authors note, the transition to a multi-level training system requires the widespread introduction of active and interactive forms of education into the educational process, aimed at increasing its effectiveness and forming general cultural and professional competencies of students. The article is devoted to the analysis of the use in the educational process of active and interactive forms of conducting classes in the conditions of a competency-based approach.